The new corporate climate leadership - Cameron, Edward; Prattico, Emilie (New York, NY : Routledge, 2022)
"This book provides a comprehensive treatment of the role of the private sector in accelerating the transition to a low-carbon, climate-resilient and inclusive world. In the lead up to and since the historic Paris Agreement on climate change, more than 6000 companies from 120 countries representing more than $36.5 trillion in revenue have made climate commitments. Examining this trend, The New Corporate Climate Leadership provides a clear synthesis of the relationship between the real economy and climate change and offers a state-of-the-art assessment of corporate initiatives that focus on greenhouse gas emissions reductions and the management of climate risk through enhanced resilience. It debates the relative merits of incremental and sequenced ambition versus radical systems change - including a critique of the prevailing capitalist approach to climate change; and provides an actionable guide to skills development for change makers in the shift towards a low carbon world. Drawing on perspectives from leading thinkers inside the private sector, across government and within civil society to truly interrogate the scale, scope, and speed of progress, this book provides a clear vision for what the next generation of corporate climate leadership should look like. Optimistic in tone, this book will be of great interest to students, scholars and practitioners of climate change and sustainable business"--
Keywords: Business enterprises -- Environmental aspects; Management -- Environmental aspects; Sustainable engineering; Corporate governance; BUSINESS & ECONOMICS / Development / Sustainable Development; NATURE / Ecology